Inferior Vena Cava Duplication with azygos vein drainage a case report - Vasconcelos,João (2015)
The authors describe the case of an inferior vena duplication with azygos vein drainage diagnosed during diagnostic venography, prior to filter introduction. In a 69 years old medical inpatient woman with hemorrhagic stroke, a left popliteal-femoroiliac DVT was diagnosed on the 20th day of admission. She was referred for vena cava filter placement. We performed a diagnostic venography with access from the right internal jugular vein. It has been possible to observe an inferior vena cava duplication with an anomalous posterior heart drainage. We placed an inferior vena cava filter in suprarrenal position, accessing the right common femoral vein. Duplication of vena cava is rare with a prevalence of 0.2-3%. Its approach in the context of placing a filter becomes an unusual challenge.